Human Resource Reform In Realizing Good Governance At The National Archives Of The Republic Of Indonesia (ANRI) - Azra Mahira; Hamka Hamka; Ridwan Rajab (Journal Of Social Science (JoSS), 2023)
Bureaucratic reform is one of the government's efforts to realize good governance. This research discusses human resource reform carried out by the National Archives of the Republic of Indonesia (ANRI) to realize Good Governance using qualitative research methods and case study approaches. The data collection technique uses primary data taken from observations and interviews with 5 informants as well as secondary data taken from the results of documentation and literature review. The results of this study can be concluded that in realizing good governance, ANRI has carried out reforms that involve overhaul, change, improvement, and structuring activities well, especially in terms of HR reform. The supporting factors of HR reform at ANRI are the support of the commitment of organizational leaders, organizational culture factors, HR management development factors, infrastructure, and budget so as to realize good governance at ANRI. However, until now ANRI does not have an assessment center for employees and there is no grand design rule on employee talent management. In addition, there is no legal umbrella or policy that applies in the implementation of rewards and punishment at ANRI. There is a strategy in overcoming obstacles to human resource reform carried out by ANRI by compiling a grand design in HR development to map competencies and organizational needs in accordance with the strategic plan so as to get an overview of future HR needs.